Predictors of COVID-19 Vaccine Acceptance Among Nigerian Medical Doctors - Nri-Ezedi CA; Okechukwu C; Ofiaeli OC; Nwaneli E; Musa S; Kida I; Adetola H; Ulasi TO (Annals of Health Research, 2022)
Background: Since its discovery in late 2019, COVID-19 has claimed approximately three million lives worldwide, causing a significant economic burden and strain on health care delivery and services. Therefore, the COVID-19 vaccine may offer the potential to promote global recovery. Objective: To determine the acceptability of the COVID-19 vaccine among Nigerian doctors and the factors influencing the acceptance.Methods: Using a cross-sectionaldesign, an anonymous online survey was administered to medical doctors across the six geopolitical zones in Nigeria between 13 January and 31 January 2021, using the health belief model (HBM). Results: Out of 830 respondents, 38.8% were willing to take the COVID-19 vaccine, 36.0% were unsure, while the remaining 26.5% refused to take the vaccine.Following adjustments, males were more likely to take the vaccine (OR = 3.357; 95% CI 2.009-5.610; p = 0.0001), whereas increasing age, higher perceived viral virulence and perceived viral infectivity were observed to be significantly associated with less likelihood of accepting the vaccine. Respondents who believed in the efficacy of ivermectin were much less likely to receive the vaccine (OR = 0.217; 95% CI 0.108-0.436; p=0.001). Concerns on vaccination safety were themain barriersto vaccine acceptability. Hypothetically addressing these concerns increased vaccine acceptance rates by approximately a third (34.6%) (p < 0.001). Conclusion: The proposed nationwide distribution of the COVID-19 vaccine may be met withpoor vaccine acceptability among Nigerian medical practitioners. Measures specifically addressing vaccine safety concerns should be provided to allay fears and enhance the acceptability of the vaccine.